Clinical Use of a Rapid Collagen Binding Assay for von Willebrand Factor Cleaving Protease in Patients with Thrombotic Thrombocytopenic Purpura - Rick, Margaret E.; Moll, Stephan; Taylor, Mark A.; Krizek, Dennis M.; White, Gilbert C., II; Aronson, David L. (Thrombosis and Haemostasis, 2002)
A simple collagen binding assay (CBA) for measuring activity of the von Willebrand factor cleaving protease in clinical samples is described, and results of fifty masked plasmapheresis samples from patients with TTP/HUS and other diseases are presented.There was 97.5% concordance between the CBA and a multimer gel assay. The CBA identified low protease activity in 78% of patients who had a clinical syndrome consistent with TTP/HUS and in 2 of 10 sick controls, giving it a positive predictive value of 0.94. The heterogeneity regarding the presence or absence of vWF protease activity in patients with TTP/HUS was confirmed by finding a low negative predictive value of 0.50 with the CBA. The CBA detected inhibitors of the protease in 26 of 29 patients (90%) with TTP/HUS and low protease activity levels. The CBA is a useful clinical assay for examining von Willebrand factor protease activity and detecting inhibitors against the protease.
Keywords: vWF protease assay; TTP; HUS; collagen; multimers